2021
DOI: 10.1093/ijnp/pyab014
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Scores Differentiating Schizophrenia From Bipolar Disorder Are Associated With Premorbid Intelligence in Schizophrenia Patients and Healthy Subjects

Abstract: Background Impairments in intelligence are more severe in patients with schizophrenia (SCZ) than in patients with bipolar disorder (BD) despite clinical and genetic similarities between the disorders. Genetic loci differentiating SCZ from BD, i.e., SCZ-specific risk, have been identified. Polygenetic [risk] scores (PGSs) for SCZ-specific risk are higher in SCZ patients than in healthy controls (HCs). However, the influence of genetic risk on impaired intelligence is poorly understood. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…All participants were of Japanese descent and had no biological first-or seconddegree relatives within their own diagnostic groups. The participants were recruited from the Schizophrenia Non-Affected Relative Project (SNARP) (Kataoka et al, 2020;Ohi et al, 2020aOhi et al, , 2020bOhi et al, , 2021aOhi et al, , 2019Ohi et al, , 2017a. The patients and their unaffected FRs were recruited from Kanazawa Medical University Hospital.…”
Section: Sample Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…All participants were of Japanese descent and had no biological first-or seconddegree relatives within their own diagnostic groups. The participants were recruited from the Schizophrenia Non-Affected Relative Project (SNARP) (Kataoka et al, 2020;Ohi et al, 2020aOhi et al, , 2020bOhi et al, , 2021aOhi et al, , 2019Ohi et al, , 2017a. The patients and their unaffected FRs were recruited from Kanazawa Medical University Hospital.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…A detailed description of the genotyping, quality control (QC), and imputation procedures applied in the study sample has been provided previously (Ohi et al, 2020a(Ohi et al, , 2020b(Ohi et al, , 2021a. Briefly, venous blood was collected from the participants, and genomic DNA was extracted from whole-blood samples.…”
Section: Genotyping and Imputationmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Accordingly, the large-scale genome-wide association study (GWAS) by Savage and colleagues 29 identified 205 genomic loci associated with intelligence, which they found to be enriched in genes expressed in the brain. Moreover, Ohi and colleagues 30 found that genetic factors differentiating schizophrenia from bipolar disorder were related specifically to low premorbid intelligence. Thus, the identification of genetic variants that contribute to risk of schizophrenia and low IQ could provide insights into the biological correlates of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2020a;Ohi et al, 2020b;Ohi et al, 2021). Brie y, venous blood was collected from the participants, and genomic DNA was extracted from whole-blood samples.…”
mentioning
confidence: 99%